Orthodontic management of a severely rotated central incisor: a case report / Saraswathy Devi Sinniah and Najiyatu Nazihah Zakaria - Sinniah, Saraswathy Devi; Zakaria, Najiyatu Nazihah (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
Background: Crowding, rotation and impaction of teeth are some of the complications of supernumeraries. This article aims to discuss the orthodontic treatment of a severely rotated upper left central incisor (UL1) secondary to an erupted mesiodens. An 18-year old Malay male presented with Class I malocclusion with severely crowded upper arch, presence of erupted mesiodens, severely rotated upper left central incisor, displaced upper left lateral incisor and upper left canine and centreline discrepancy. Methods: He had a combination of segmented arch and couple force mechanics to correct severely rotated central incisors. Following anchorage reinforcement, the upper mesiodens and the upper right first premolar was extracted. Subsequently, treatment was continued with conventional straight wire mechanics. Results: The severely rotated upper left central incisor was successfully corrected, and the upper arch crowding was resolved. The fixed appliances were debonded and he was provided with upper dual retention. He had gingival recession Type 1 at UL2 due to the bony defect. Conclusion: Severe crowding can be managed with segmented arch mechanics without any detrimental effects using low forces and good planning. Further periodontal consultation and management were required for the treatment of UL2.